Suppression of Amygdalar Endocannabinoid Signaling by Stress Contributes to Activation of the Hypothalamic-Pituitary-Adrenal Axis - Hill, Matthew N. (2009)
Endocannabinoids inhibit hypothalamic-pituitary-adrenal (HPA) axis activity; however, the neural substrates and pathways subserving this effect are not well characterized. The amygdala is a forebrain structure that provides excitatory drive to the HPA axis under conditions of stress. The aim of this study was to determine the contribution of endocannabinoid signaling within distinct amygdalar nuclei to activation of the HPA axis in response to psychological stress. Exposure of rats to 30 min restraint stress increased the hydrolytic activity of fatty acid amide hydrolase (FAAH) and concurrently decreased content of the endocannabinoid/CB(1) receptor ligand N-arachidonylethanolamine (anandamide; AEA) throughout the amygdala. In stressed rats, AEA content in the amygdala was inversely correlated with serum corticosterone concentrations. Pharmacological inhibition of FAAH activity within the basolateral amygdala complex (BLA) attenuated stress-induced corticosterone secretion; this effect was blocked by co-administration of the CB(1) receptor antagonist AM251, suggesting that stress-induced decreases in CB(1) receptor activation by AEA contribute to activation of the neuroendocrine stress response. Local administration into the BLA of a CB(1) receptor agonist significantly reduced stress-induced corticosterone secretion, while administration of a CB(1) receptor antagonist increased corticosterone secretion. Taken together, these findings suggest that the degree to which stressful stimuli reduce amygdalar AEA/CB1 receptor signaling contributes to the magnitude of the HPA response.